2009
DOI: 10.1007/s11802-009-0077-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia on dopamine concentration and the immune response of White Shrimp (Litopenaeus vannamei)

Abstract: Effects of hypoxia on the dopamine concentration and the immune response of White Shrimp Litopenaeus vannamei were studied. The results showed that hypoxia had significant effects on the concentration of dopamine (DA) in the haemolymph, haemocyte count, phenoloxidase activity, phagocytic activity of haemocytes and bacteriolytic and antibacterial activity in the haemolymph (P<0.05). The concentration of the dopamine in haemolymph reached its maximum in the 3.0 and 1.5 mg L -1 DO groups at 12 h and 6 h, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…We also found that the mortality rate ( z ) was negatively related to dissolved oxygen, indicating a negative effect of low dissolved oxygen on shrimp survival as reported by Allan and Maguire (), Jiang, Pan and Bo () and Hu, Luqing and Futao ().…”
Section: Discussionsupporting
confidence: 84%
“…We also found that the mortality rate ( z ) was negatively related to dissolved oxygen, indicating a negative effect of low dissolved oxygen on shrimp survival as reported by Allan and Maguire (), Jiang, Pan and Bo () and Hu, Luqing and Futao ().…”
Section: Discussionsupporting
confidence: 84%
“…L. vannamei following 48-h exposure to hypoxia at 4.00 kPa decreased its THC by 40.4% (Mikulski et al 2000). Hu et al (2009) found THC and the hyaline cells decreased in the 7.85 and 3.93 kPa DO after 12 and 24 h, respectively. These observations indicated that hypoxia suppressed their immune abilities, however, in this present study the exposure time was only 24 h, the reductions in THC and hyaline cells could not all be due to the reduction of immune, it could partly respond appropriately to an impending condition deterioration threat to health.…”
Section: Discussionmentioning
confidence: 78%
“…However, Tan et al () conducted a simulated transport test using large‐size (6.32 ± 0.21 g) sea cucumbers in laboratory, and the levels of NE and DOP both notably increased during 3 hr of damp transport or water transport. In addition, both air exposure exerted on the octopus Eledone cirrhosa (Malham, Lacoste, Gelebart, Cueff, & Poulet, ) and hypoxic stress on white shrimp, Litopenaeus vannamei (Hu, Pan, & Jing, ), resulted in elevation of catecholamine amounts. Given that the neuroendocrine response changed with the nature and extent of stressor, all the juveniles in this study were stored at a lower temperature, maintained using bagged ice and foam thermal insulation boxes.…”
Section: Discussionmentioning
confidence: 99%